Influence of biodegraded bark extracts of Anacardium occidentale on survival of Meloidogyne incognita infecting cabbage plants - Fabiyi, Oluwatoyin (Journal of Tropical Agriculture, 2024)
Plant parasitic nematodes (PPNs) cause great damage to all agricultural crops; they infect all plant parts and cause reduction in yield. Synthetic nematicides have been used lately to combat the menace of PPNs on farmlands. The drawbacks of synthetic nematicides gave rise to interest in alternative methods of managing plant parasitic nematodes. In this regard, compounds from biodegraded as well as fresh stem bark of (cashew) Anacardium occidentale were extracted, isolated and partially characterized. The crude extracts and isolates were tested for their nematicidal activity in laboratory and field experiments. Significant (p<0.05) differences were observed in the activity of the extracts and isolates. The isolated compounds from A. occidentale biodegraded stem bark extract (ANCO/BDG/CMP) exhibited higher juvenile mortality and reduced egg hatch in the laboratory while the activity of the isolated compound from fresh bark (ANCO/ FRS/CMP) extract was significantly lower. The crude extracts ANCO/FRS/CRD and ANCO/BDG/CRD had weaker nematicidal activity. Meloidogyne incognita population was notably low after harvest in all treated cabbage plants on the field. Spectroscopic results revealed that microbial action during biodegradation of the stem bark produced a different compound having nematicidal properties.